Irrigation and fruit canopy position modify oil quality of olive trees (cv. Frantoio). (15th February 2017) - Caruso, Giovanni; Gucci, Riccardo; Sifola, Maria Isabella; Selvaggini, Roberto; Urbani, Stefania; Esposto, Sonia; Taticchi, Agnese; Servili, Maurizio
Abstract: BACKGROUND: Fruit development and oil quality in Olea europaea L. are strongly influenced by both light and water availability. In the present study, the simultaneous effects of light environment and irrigation on fruit characteristics and oil quality were studied in a high‐density orchard over two consecutive years. Olive fruits were harvested from three canopy positions (intercepting approximately 64%, 42% and 30% of above canopy radiation) of fully‐productive trees subjected to full, deficit or complementary irrigation. RESULTS: Fruits receiving 61–67% of above canopy radiation showed the highest fruit weight, mesocarp oil content and maturation index, whereas those intercepting only 27–33% showed the lowest values. Palmitoleic and linoleic acids increased in oils obtained from fruits exposed to high light levels, whereas oleic acid and the oleic‐linoleic acid ratio decreased. Neither canopy position, nor irrigation affected K 232, K 270, Δ K and the concentration of lignan in virgin olive oils (VOOs). Total phenols, 3, 4‐DHPEA‐EDA [2‐(3, 4‐hydroxyphenyl)ethyl (3S, 4E)‐4‐formyl‐3‐(2‐oxoethyl)hex‐4‐enoate] and p ‐HPEA‐EDA (decarboxymethyl ligstroside‐aglycone) increased in VOOs produced from fruits harvested from the top of the canopy, whereas full irrigation decreased total phenols and 3, 4‐DHPEA‐EDA concentrations with respect to the complementary irrigation treatment. CONCLUSION: Light and water availability are crucial not only for tree productivity, but also they clearly affect olive oil quality. © 2017 Society of Chemical Industry